Determinants of performance in the isocitrate dehydrogenase of Escherichia coli. - Dean, A. M. (Cold Spring Harbor Laboratory Press, 1996)
The substrate specificity of the NADP-dependent isocitrate dehydrogenase of Escherichia coli was investigated by combining site-directed mutagenesis and utilization of alternative substrates. A comparison of the kinetics of the wild-type enzyme with 2R-malate reveals that the gamma-carboxylate of 2R,3S-isocitrate contributes a factor of 12,000,000 to enzyme performance. Analysis of kinetic data compiled for 10 enzymes and nine different substrates reveals that a factor of 1,650 can be ascribed to the hydrogen bond formed between S113 and the gamma-carboxylate of bound isocitrate, a factor of 150 to the negative charge of the gamma-carboxylate, and a factor of 50 for the gamma-methyl. These results are entirely consistent with X-ray structures of Michaelis complexes that show a hydrogen bond positions the gamma-carboxylate of isocitrate so that a salt bridge can form to the nicotinamide ring of NADP.